IMPACT OF INNOVATIONS ON THE PRODUCT MARKET COMPETITIVE DEVELOPMENT (International Journal of Innovative Technologies in Economy, 2018)
Competitive product markets are characterized by aiming at complete consumers’ needs satisfaction, flexible market price making, freedom of economic activity and entrepreneurship, free entry and exit from a market, fair trading and business practices etc. The highest values for the companies functioning at the competitive markets are consumers and consumer needs. Accordingly, all the decisions related to the companies’ activity are being taken not based on the entrepreneurs’ ambitions, but from the perspective of the consumer as the agent of future income and profits. One of the essential characteristics of the markets competitive development is ability of the market players to optimize costs, minimize prices, and improve product quality for the maximum consumer satisfaction. Innovations are one of the means for providing competitive development path. However, the essence of innovations is not only introducing something new, some quality changes of the entrepreneurship activity. This economic category may manifest itself as a barrier for entry into product markets, and may cause emerging of innovative monopolies that eventually influence competitive development. Presented article is dedicated to the outcomes of innovative activity on the marketplace. Interconnections between the competitive environment and innovativeness are being investigated, and as the result, innovativeness is proven a method of overcoming competitive pressure, achieving competitive advantages at the market. It is determined that innovativeness depends on the companies’ size, as the financial capacity for innovations and availability of the labour potential concentrated in the innovative area are higher within big companies. As well the need for innovativeness as the mean for attaining competitive advantages depends both on the industry type and the product market characteristics, where a company is functioning, as there are no needs for competitive advantages at monopolistic markets. Innovations may also appear in natural monopolies as the result of introducing some regulatory policies. Also the causality between companies’ pursuance of uniqueness, the level of national competitiveness – and the innovations is being investigated, as well as the time lag between introduction of innovations and gaining some competitive advantages at the market. Understanding mutual influences of innovations and product markets competitive development is the clue for taking proper decisions by regulatory bodies with respect to markets development. Appearance of innovative monopolies aggravate the demand for regulatory bodies control over product markets development with the purpose of preventing excessive use of the market power by innovative monopolies.